# Power by using the principle of Mathematical Induction that `n!>= 2^(n-1)` for every positive integer n.

*print*Print*list*Cite

### 1 Answer

`n! >= 2^(n-1) `

`n = 1`

`LHS = 1! =1`

`RHS = 2^(1-1) = 1`

`LHS = RHS`

For `n = 1` result is true.

Let us assume that for n = p where `p>=1` and a positive integer the result is true.

`p!>=2^(p-1)`

`n = p+1`

`p!>=2^(p-1)` multiply both sides by `(p+1` ).

`p!xx(p+1)>=2^(p-1)xx(p+1)`

`(p+1)!>= 2^(p-1)xx(p+1)`

`p>=1` therefore `(p+1)>=2`

Therefore;

`(p+1)!>= 2^(p-1)xx2` is valid

`(p+1)!>= 2^(p+1-1)`

So for n = p+1 the result is true.

** So from mathematical induction it is proved that **`n! >= 2^(n-1) `

**Sources:**